Potential of Ammoniated Citronella Distillation Waste as an Alternative Fiber Source to Replace Grass in Ruminant Diets - Elihasridas; Muhammad Ahsan Naeem; Simel Sowmen; Qurrata Aini (Andalasian Livestock, 2026)
This study evaluated the effect of substituting grass with ammoniated citronella waste supplemented with cassava leaves, phosphorus, and zinc minerals on nutrient digestibility and rumen fluid characteristics in vitro. The study used a completely randomized design with five treatments and four replications: R0 = 100% grass; R1 = 75% grass + 25% ammoniated citronella waste; R2 = 50% grass + 50% ammoniated citronella waste; R3 = 25% grass + 75% ammoniated citronella waste; and R4 = 100% ammoniated citronella waste. The variables observed included the digestibility of dry matter, organic matter, and crude protein, as well as pH, NH₃, and VFA. The results showed that the treatments significantly affected the digestibility of dry matter, organic matter, crude protein, NH₃, and VFA, but did not significantly affect rumen fluid pH. The highest digestibility of dry matter, organic matter, and VFA was obtained in treatment R3, while the highest digestibility of crude protein and NH₃ was obtained in treatment R4. The pH value of the rumen fluid in all treatments remained within the normal range. It was concluded that ammoniated citronella waste supplemented with cassava leaves, phosphorus minerals, and zinc could be used as an alternative fiber source to replace grass, with an optimal substitution level of 75% based on dry matter and organic matter digestibility and rumen fermentability.